1998
DOI: 10.1021/ja980089x
|View full text |Cite
|
Sign up to set email alerts
|

Sigma Bond Activation by Cooperative Interaction with ns2 Atoms:  B+ + nH2

Abstract: The reactions of B+ + nH2 to produce BH2 +(H2) n - 1 have been studied by high-level ab initio techniques. The reaction mechanism and associated activation energy is found to depend dramatically on the number of H2 molecules present. For n = 1, the reaction proceeds stepwise:  first breaking the H2 bond and forming one BH bond followed by forming the second BH bond. This process has an activation energy of about 57 kcal/mol. For n = 2, the reaction proceeds via a pericyclic mechanism though a planar cyclic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
57
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(63 citation statements)
references
References 16 publications
6
57
0
Order By: Relevance
“…Sharp et al found that the electrostatically bound Al + -H 2 complex lies 13.1 kcal/ mol lower in energy than the inserted HAlH + structure. 12,13 Although the insertion barrier is also predicted to be lowered for the larger Al + -͑H 2 ͒ n clusters, it remains appreciable ͑53.2 kcal/ mol for n =3͒. 10 The corresponding reaction for the isovalent B + ion, where the inserted HBH + form is 55.9 kcal/ mol more stable than the B + -H 2 complex, was found to be expedited in B + -͑H 2 ͒ n clusters, with a significant lowering in the insertion barrier for n =3 compared to n =1 ͑3 kcal/ mol vs 56 kcal/ mol͒.…”
Section: Introductionmentioning
confidence: 99%
“…Sharp et al found that the electrostatically bound Al + -H 2 complex lies 13.1 kcal/ mol lower in energy than the inserted HAlH + structure. 12,13 Although the insertion barrier is also predicted to be lowered for the larger Al + -͑H 2 ͒ n clusters, it remains appreciable ͑53.2 kcal/ mol for n =3͒. 10 The corresponding reaction for the isovalent B + ion, where the inserted HBH + form is 55.9 kcal/ mol more stable than the B + -H 2 complex, was found to be expedited in B + -͑H 2 ͒ n clusters, with a significant lowering in the insertion barrier for n =3 compared to n =1 ͑3 kcal/ mol vs 56 kcal/ mol͒.…”
Section: Introductionmentioning
confidence: 99%
“…2 From a third viewpoint, LiH 2 Ϫ is the simplest anion having a geometry which allows the transition state region of a neutral system to be accessed by photodetachment. 5 To effectively weaken and ultimately break an H 2 bond, the node of an occupied molecular orbital needs to bisect the H 2 molecule. Kemper et al 4 used mass spectrometric techniques to study the interaction of B ϩ ͑isoelectronic with Li Ϫ ͒ with H 2 and reported that the activation energy for forming BH 2 ϩ could be reduced from near 60 kcal/mol when only one H 2 molecule was present to about 2 kcal/mol through the interaction of two additional H 2 molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The first theoretical investigation of LiH 2 Ϫ was performed only at the self-consistent field ͑SCF͒ level, 8 where the ion was calculated to be linear but not stable with respect to the lowest energy dissociation products, Li Ϫ ϩH 2 . 4,5 In addition, Senekowitsch and Romus pointed out that the energy of the transition state region may be very close to that of the neutral LiH 2 system at the same geometry, a situation which has no analog in the B ϩ ϩH 2 system. Although it was shown that LiH 2 Ϫ could be formed from LiHϩH Ϫ without a barrier, 1 the barrier for formation from Li Ϫ ϩH 2 has not been considered in detail previously.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest that the [BH 2 ] + system possesses two stable structures, the electrostatically bound B + -H 2 complex (Figure 1(a)), and a covalently bound HBH + form (Figure 1(b)). [17][18][19] The electrostatic complex has a C 2v equilibrium structure, as favoured by the charge-quadrupole interaction between the B + cation and the H 2 molecule. Interconversion between the electrostatic complex (Figure 1(a)) and the more stable covalent form (Figure 1(b)) entails surmounting a 252 kJ mol −1 barrier associated with a change in electron configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Interconversion between the electrostatic complex (Figure 1(a)) and the more stable covalent form (Figure 1(b)) entails surmounting a 252 kJ mol −1 barrier associated with a change in electron configuration. 18 Whereas, for B + -H 2 the valence electron configuration is 2a 2 1 3a 2 1 (corresponding to ground state B + interacting with ground state H 2 ), the covalently bound HBH + molecule has an 2a 2 1 1b 2 2 electron configuration and correlates with an electronically excited B + ion (2s 1 2p 1 z configuration). There have been several previous experimental studies of the B + +H 2 system, including ion-molecule reactions, 20 reactive scattering, [21][22][23] and chemiluminescence.…”
Section: Introductionmentioning
confidence: 99%